Synthesis and evaluation of symmetric acyclic nucleoside bisphosphonates as inhibitors of the Plasmodium falciparum, Plasmodium vivax and human 6-oxopurine phosphoribosyltransferases and the antimalarial activity of their prodrugs. Issue 15 (1st August 2017) - Špaček, Petr; Keough, Dianne T.; Chavchich, Marina; Dračínský, Martin; Janeba, Zlatko; Naesens, Lieve; Edstein, Michael D.; Guddat, Luke W.; Hocková, Dana
Graphical abstract: Abstract: Two new series of symmetric acyclic nucleoside bisphosphonates (ANbPs) have been synthesised as potential inhibitors of the Plasmodium falciparum ( Pf ) and vivax ( Pv ) 6-oxopurine phosphoribosyltransferases . The structural variability between these symmetric ANbPs lies in the number of atoms in the two acyclic linkers connecting the N 9 atom of the purine base to each of two phosphonate groups and the branching point of the acyclic moiety relative to the purine base, which occurs at either the alpha or beta positions. Within each series, six different 6-oxopurine bases have been attached. In general, the ANbPs with either guanine or hypoxanthine have lower Ki values than for those containing either the 8-bromo or 7-deaza 6-oxopurine bases. The lowest Ki values obtained for the two parasite enzymes were 0.1 μM ( Pf ) and 0.2 μM ( Pv ) for this series of compounds. Two phosphoramidate prodrugs of these inhibitors exhibited antimalarial activity against Pf in infected erythrocyte cell culture with IC50 values of 0.8 and 1.5 μM. These two compounds exhibited low cytotoxicity in human A549 cells having CC50 values of >300 μM resulting in an excellent selectivity index.